Combination of Ephedra sinica stems and Terminalia chebula fruits produces new ephedrine derivatives in vivo that diminish the permeability to BBB while retaining airway dilation and hepatoprotective effects. (1st March 2022) - Duan, Shen; Cui, Xue-Ying; Wang, Xin-Yao; Shan, Cheng-Bin; Ma, Chao-Mei
Abstract: Ethnopharmacological relevance: The stems of Ephedra sinica and the fruits of Terminalia chebula are combined using in traditional Mongolian medicine formula "Gurigumu-7" for liver diseases. E. sinica stems contains ephedrine with broncho-dilatory activity. However, ephedrine can pass through the blood-brain barrier (BBB) and excite the central nervous system (CNS) to cause insomnia and restlessness. Aim of the study: The present study was to investigate the structures and bioactivities of new compounds formed in vivo after co-administration of E. sinica stems and T. chebula fruits. Materials and methods: Pharmacokinetic investigation was carried out in rats. A parallel artificial membrane permeability measurement system was used to determine BBB permeability. Ex vivo experiments using tracheal rings of guinea pig was performed to examine the tracheal relaxation effect. In vivo hepatoprotective tests were carried out in Tg (fabp10a: dsRed) liver transgenic zebrafish. The fluorescent probe, 2, 7-dichlorodihydrofluorescein diacetate, was used to measure reactive oxygen species, and UHPLC-MS was used to determine glutathione concentrations after derivatization with N-ethylmaleimide. Results: New ephedrine derivatives (1 and 2 ) formed in vivo and reached their maximum serum concentrations at 0.5 h after administration of the two herbal drugs. Compounds 1 and 2 showed lower BBB permeability than ephedrine, suggesting that they have less adverse effects on the CNS. Compounds 1 and 2 relaxed the tracheal rings and had strong hepatoprotective effect on transgenic zebrafish with liver specific expression of RFP. Compounds 1 and 2 significantly reduced the level of reactive oxygen species while increasing that of glutathione in thioacetamide-treated zebrafish, which might be the hepatoprotective mechanism. Conclusion: These results provided evidences that the chemical constituents in various herbal drugs in a medicinal formula can interact to generate new compounds with fewer side effects and increased or additive bioactivity. Graphical abstract: Image 1